CD8+ T cells and IFN-γ induce autoimmune myelofibrosis in mice. (May 2018) - Yao, Yuan; Li, Liang; Yang, Shu-Han; Gao, Cai-Yue; Liao, Liang-Huan; Xie, Yu-Qing; Yin, Xue-Ying; Yang, Yan-Qing; Fei, Yun-Yun; Lian, Zhe-Xiong
Abstract: Myelofibrosis usually occurs either as a part of a myelodysplastic syndrome or in conjunction with neoplasia. It is not commonly thought of an autoimmune disease. We reported that p40 −/− IL-2Rα −/− (interleukin-12p40 and interleukin-2 receptor alpha double knockout) mice, a mouse model of human primary biliary cholangitis, exhibited features consistent with autoimmune myelofibrosis, including anemia associated with bone marrow fibrosis, and extramedullary hematopoiesis (EMH) including LSK (Lineage - c-Kit + Sca-1 + ) cells in spleen, liver and peripheral blood. There were also increased LSK cells in bone marrow but they demonstrated impaired hematopoiesis. Importantly effector memory T cells that infiltrated the bone marrow of p40 −/− IL-2Rα −/− mice manifested a higher ability to produce IFN-γ. CD8 + T cells, already known to play a dominate role in portal inflammation, were also key for bone marrow dysregulation and EMH. IFN-γ was the key cytokine that induced bone marrow fibrosis, bone marrow failure and EMH. Finally anti-CD8α antibody therapy fully protected p40 −/− IL-2Rα −/− mice from autoimmune myelofibrosis. In conclusion, our results demonstrate that CD8 + T cells and IFN-γ are associated with autoimmune myelofibrosis, a finding that may allow targeting of CD8 + T cells and IFN-γ as a therapeutic targets. Highlights: p40 −/− IL-2Rα −/− mice displayed anemia and extramedullary hematopoiesis. p40 −/− IL-2Rα −/− mice had myelofibrosis with increased IFN-γ producing T cells. CD8 + T cells and IFN-γ promoted the development of autoimmune myelofibrosis. Depletion of CD8 + T cells successfully ameliorated autoimmune myelofibrosis.